MR characterization of hepatic storage iron in transfusional iron overload. Issue 2 (29th May 2013) - Tang, Haiying; Jensen, Jens H.; Sammet, Christina L.; Sheth, Sujit; Swaminathan, Srirama V.; Hultman, Kristi; Kim, Daniel; Wu, Ed X.; Brown, Truman R.; Brittenham, Gary M.
Abstract : Purpose: To quantify the two principal forms of hepatic storage iron, diffuse, soluble iron (primarily ferritin), and aggregated, insoluble iron (primarily hemosiderin) using a new MRI method in patients with transfusional iron overload. Materials and Methods: Six healthy volunteers and 20 patients with transfusion‐dependent thalassemia syndromes and iron overload were examined. Ferritin‐ and hemosiderin‐like iron were determined based on the measurement of two distinct relaxation parameters: the "reduced" transverse relaxation rate, RR2, and the "aggregation index, " A, using three sets of Carr‐Purcell‐Meiboom‐Gill (CPMG) datasets with different interecho spacings. Agarose phantoms, simulating the relaxation and susceptibility properties of tissue with different concentrations of dispersed (ferritin‐like) and aggregated (hemosiderin‐like) iron, were used for validation. Results: Both phantom and in vivo human data confirmed that transverse relaxation components associated with the dispersed and aggregated iron could be separated using the two‐parameter (RR2, A) method. The MRI‐determined total hepatic storage iron was highly correlated ( r  = 0.95) with measurements derived from biopsy or biosusceptometry. As total hepatic storage iron increased, the proportion stored as aggregated iron became greater. Conclusion: This method provides a new means for noninvasive MRI determination of the partition of hepatic storage iron between ferritin and hemosiderin in iron overload disorders.J. Magn. Reson. Imaging 2014;39:307–316 . ©2013 Wiley Periodicals, Inc .